ANALISIS FAKTOR PENYEBAB BANJIR DI ACEH SELATAN (STUDI KASUS : 17 MEI 2021) - Kurnia Dea (Megasains, 2022)
Flash floods that hit five sub-districts of South Aceh occurred on May 17, 2021 since 15.11 WIB due to the overflow of the Lae Ordi river. The accumulated rainfall for 24 hours was 158.8 mm/day at the Cut Ali ARG which was included in the heavy rain category. Atmospheric dynamics analysis such as global, regional, and local scales is needed to determine the atmospheric conditions during a flood event. Himawari-8 satellite data is also needed to see the growth of this heavy rain-producing cloud. The results of the analysis show that there is no influence of the MJO on the formation of convective clouds. Generally, the wind blows from the southwest until west with a high water vapor content with a fairly warm sea surface temperature and a convergence pattern is found around the northern waters of Java Island and a negative divergence in the 1000-200 mb layer which supports the pattern of convective cloud formation. Based on the Himawari-8 satellite image, it also shows the growth of convective clouds from 02.00 UTC to 17.30 UTC. It can be seen that the cloud top temperature reaches -55 °C and the cloud temperature contour reaches -72.5 °C.